PEMBERDAYAAN MASYARAKAT MELALUI AGENT OF CHANGE PENCEGAHAN STUNTING DI KELURAHAN PILOLODAA KECAMATAN KOTA BARAT KOTA GORONTALO - Aswad, Ahmad; Adam, Lusiane; Suma, Juwita; Abdullah, Dirman (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
Stunting is a condition where a toddler has a length or height that is less than normal when compared to his age. Toddlers with growth delays may be at risk of decreased intelligence, decreased productivity and increased risk of degenerative diseases in the future. The purpose of this community service is to increase mothers' knowledge about nutritious food before pregnancy and after childbirth, use of clean water and sanitation. Pilolodaa Village was chosen as the location for the community service because it is one of the working areas of the West City Health Center which has the highest number of stunted children under five with a percentage of 28.46%. The method of implementing community service is carried out in the form of counseling using lecture methods, discussions, consultations, freezes, empowerment, mentoring and evaluation of knowledge about stunting prevention through a series of activities, namely licensing, coordination with the Kota Barat Health Center and Pilolodaa Village, preparing tools, media and places to use for program implementation. The results of the community service were an increase in knowledge about stunting prevention and an increase in skills in preparing nutritious food in the Pilolodaa Community Village, Kota Barat District, Gorontalo City.